Optimal Sizing of Micro Hydropower to Improve Hybrid Renewable Power System - Syafii Syafii; Heru Dibyo Laksono; Novizon Novizon; Rahmad Fahreza (Proceeding of the Electrical Engineering Computer Science and Informatics, 2020)
This paper presents an analysis of optimal micro hydropower (MH) capacity of hybrid systems to improve renewable energy based power systems. The electricity system was designed by considering river water flow data and solar radiation data at the research location, Andalas University. Optimal results obtained for the configuration of the Grid, MH, and PV with a head height of 30 m and a flow rate of 800 L/s with the lowest COE value of $ 0.065. As an optimal sizing system has been able to increase the composition of renewable energy generation in the Unand electrical network. The renewable energy fraction has increased from 26.4% to 36.5%. Therefore, determining the optimal capacity will increase the use of renewable energy generation. Conversely, an increase in electricity supply from renewable energy plants will reduce electricity consumption from the PLN grid. The latest excess power generation at a low load can be sold to the PLN grid